DAYA DUKUNG LINGKUNGAN TERHADAP TRADISI MEGALITIK PADA MASYARAKAT DAYAK Dl KABUPATEN KUTAI KERTANEGARA, PROVINSI KALIMANTAN TIMUR - Astiti, Ni Komang Ayu (Naditira Widya, 2007)
Kalimantan, particularly the regency of Kutai Kertanegara, is one of the dispersal areas of the Austronesian culture in Indonesia. Among the cultural remains found in the archipelago, which date back to the prehistoric period, are megalithic structures that are related to the traditions of burial, ancestor worship, and belief to other supernatural powers. Wood is the main forest product, which can be found in almost half of the Kutai Kertanegara Regency area. The Dayak communities in this area have long since had the knowledge of the technology to exploit this natural source to support their daily needs as well as the megalithic tradition. The use of wood to sustain the tradition with megalithic characteristics in this area is evidenced by burial containers (tempelak), upright stones to tie sacrificial animals (belontang), structures to carry out worshipping activities (bale banci, ancak, bale /irong), traditional houses (rumah lamin), animal totems (hornbills, marine animals), and tombstones (tombstones with engravings of human face, or flora and fauna).